Performance Evaluation of Effluent Treatment Plant (OCM Pvt. Ltd., Amritsar) - Kaur, Ramandeep (My University, 2025)
Performance Evaluation of Effluent Teatment Plant was conducted at OCM Pvt.Ltd.Amritsar during the period July 2024 - June2025. The basic principles of Software NOW, its application for handling purchase and sale, warehouse modules and meeting the major requirements of textile industry were thoroughly learnt.Influent (from inlet) and effluent(from outlet) were analyzed twice weekly from Dec2024 to May 2025 (6 months) for the parameters pH, temperature, Total dissolved and suspended solids, BOD and COD. The study has shown a possibility to work further on techniques of TDS removal, kinetics development, techno-economics of treatment etc
Keywords: Industrial Effluent; Effluent Quality; Treatment Plant; Textile Industry; BOD; TDS